Electrochemical Studies and Inhibitory Effects of Millet Extract on Copper for Prolonged Service Life - Fayomi, Ojo Sunday Isaac (ABUAD Journal of Engineering Research and Development (AJERD), 2025)
This research assesses the efficacy of millet extract as a copper corrosion inhibitor under exposure to 1M hydrochloric acid (HCl) to provide an eco-friendly substitute to the use of manmade corrosion inhibitors. Open Circuit Potential (OCP), Linear Sweep Voltammetry (LSV), and Tafel polarization techniques were employed under various temperatures (30°C - 50°C) to examine the performance of various concentrations of millet extract (0 mL, 0.1 mL 0.2 mL, and 0.3 mL). The results showed a significant decrease in both the current density (Jcorr) and the corrosion rate (CR) as the concentration of the inhibitor was raised. The highest percentage inhibition was about 98% using the 0.3 mL concentration, showing a very strong protection. The findings of the adsorption study showed that the inhibitor follows both the Langmuir and Freundlich adsorption isotherms, inferring the possibility of multilayer adsorption on the copper surface. The formation of a protective film that prevents the dissolution of the metal was supported by the optical micrographs.